Neurologic manifestations in hospitalized patients with COVID-19: The ALBACOVID registry. (25th August 2020) - Romero-Sánchez, Carlos Manuel; Díaz-Maroto, Inmaculada; Fernández-Díaz, Eva; Sánchez-Larsen, Álvaro; Layos-Romero, Almudena; García-García, Jorge; González, Esther; Redondo-Peñas, Inmaculada; Perona-Moratalla, Ana Belén; Del Valle-Pérez, José Antonio; Gracia-Gil, Julia; Rojas-Bartolomé, Laura; et al.
Abstract : Objective: The coronavirus disease 2019 (COVID-19) has spread worldwide since December 2019. Neurologic symptoms have been reported as part of the clinical spectrum of the disease. We aimed to determine whether neurologic manifestations are common in hospitalized patients with COVID-19 and to describe their main characteristics. Methods: We systematically reviewed all patients diagnosed with COVID-19 admitted to the hospital in a Spanish population during March 2020. Demographic characteristics, systemic and neurologic clinical manifestations, and complementary tests were analyzed. Results: Of 841 patients hospitalized with COVID-19 (mean age 66.4 years, 56.2% men), 57.4% developed some form of neurologic symptom. Nonspecific symptoms such as myalgias (17.2%), headache (14.1%), and dizziness (6.1%) were present mostly in the early stages of infection. Anosmia (4.9%) and dysgeusia (6.2%) tended to occur early (60% as the first clinical manifestation) and were more frequent in less severe cases. Disorders of consciousness occurred commonly (19.6%), mostly in older patients and in severe and advanced COVID-19 stages. Myopathy (3.1%), dysautonomia (2.5%), cerebrovascular diseases (1.7%), seizures (0.7%), movement disorders (0.7%), encephalitis (n = 1), Guillain-Barré syndrome (n = 1), and optic neuritis (n = 1) were also reported, but less frequent. Neurologic complications were the main cause of death in 4.1% of all deceased study participants. Conclusions: Neurologic manifestations are common in hospitalized patients with COVID-19. In our series, more than half of patients presented some form of neurologic symptom. Clinicians need to maintain close neurologic surveillance for prompt recognition of these complications. The mechanisms and consequences of severe acute respiratory syndrome coronavirus type 2 neurologic involvement require further studies.